PENDAMPINGAN BUDIDAYA IKAN KOI SISTEM KOLAM AIR DERAS DI WISATA BOONPRING KABUPATEN MALANG, JAWA TIMUR - Zubaidah, Anis; Hariyadi (Jurnal Abdi Insani, 2024)
The development of swift water cultivation systems provides various advantages, including high dissolved oxygen, sufficient natural feed, high stocking density, and lower production costs. This technology can be developed among fish farming groups, especially those who have access to extensive water sources. The implementation of this community service program aims to distribute koi fish cultivation technology using a fast water system to the community, especially in the Boonpring tourist area, Sanankerto Village, Malang Regency. The method used is to provide assistance to partners in intensive koi fish cultivation technology using a fast water pond system. The results obtained are the implementation of community service activities carried out by the activity implementation team at the Boon Pring Tourism Village, as well as increasing public understanding regarding optimizing the management of koi fish cultivation land using a fast water system. The survey results show that there has been a 30% increase in public understanding regarding fast water system koi fish cultivation. The conclusion of this activity is that the technology for cultivating koi fish using a fast water system has been successfully implemented at the Boonpring tourist attraction, Sanankerto Village, Malang Regency.